2006
DOI: 10.4049/jimmunol.177.1.372
|View full text |Cite
|
Sign up to set email alerts
|

Signal Regulatory Protein Molecules Are Differentially Expressed by CD8− Dendritic Cells

Abstract: A normalized subtracted gene expression library was generated from freshly isolated mouse dendritic cells (DC) of all subtypes, then used to construct cDNA microarrays. The gene expression profiles of the three splenic conventional DC (cDC) subsets were compared by microarray hybridization and two genes encoding signal regulatory protein β (Sirpβ1 and Sirpβ4) molecules were identified as differentially expressed in CD8− cDC. Genomic sequence analysis revealed a third Sirpβ member localized in the same gene clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 47 publications
9
85
0
Order By: Relevance
“…In the mouse and human systems, the cDC subsets can be distinguished on the basis of CD11b and SIRPa expression. 29,30 In vitro, the CD1b/c 1 cDCs expressed high levels of CD11b and SIRPa, while the CLEC9A 1 cDC expressed low levels of CD11b and SIRPa (Figure 1d), similar to their in vivo counterparts. 29,30 Unlike their in vivo counterparts, the CD123 1 pDCs did not express CD304 (BDCA4) and the CLEC9A 1 cDCs did not express CD141 (BDCA3) (data not shown).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In the mouse and human systems, the cDC subsets can be distinguished on the basis of CD11b and SIRPa expression. 29,30 In vitro, the CD1b/c 1 cDCs expressed high levels of CD11b and SIRPa, while the CLEC9A 1 cDC expressed low levels of CD11b and SIRPa (Figure 1d), similar to their in vivo counterparts. 29,30 Unlike their in vivo counterparts, the CD123 1 pDCs did not express CD304 (BDCA4) and the CLEC9A 1 cDCs did not express CD141 (BDCA3) (data not shown).…”
Section: Resultsmentioning
confidence: 65%
“…29,30 In vitro, the CD1b/c 1 cDCs expressed high levels of CD11b and SIRPa, while the CLEC9A 1 cDC expressed low levels of CD11b and SIRPa (Figure 1d), similar to their in vivo counterparts. 29,30 Unlike their in vivo counterparts, the CD123 1 pDCs did not express CD304 (BDCA4) and the CLEC9A 1 cDCs did not express CD141 (BDCA3) (data not shown). However, it has recently been shown that the CD8 1 cDCs in mouse and the BDCA3 1 cDCs in human blood uniquely express XCR1.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The plasmacytoid dendritic cell (pDC) and two conventional dendritic cell (cDC) subsets defined based on CD8␣ and Sirp␣ expression: the CD8 lo Sirp␣ hi/ϩ cDCs (Ϸ30% of cDCs, Sirp␣ ϩ TcDCs hereafter) and the CD8 hi Sirp␣ lo/Ϫ cDCs (Ϸ70% of cDCs, Sirp␣ Ϫ TcDCs hereafter) (20,21). Sirp␣ Ϫ TcDCs develop from intrathymic lymphoid precursors (22,23).…”
Section: Central Tolerance Is Established Through Negative Selection mentioning
confidence: 99%
“…Three of the major DC subsets in mouse secondary lymphoid organs are as follows: (i) CD11c high CD8 − DCs, (ii) CD11c high CD8 + DCs, and (iii) CD11c int CD45RA + Gr1 + plasmacytoid DCs (PDCs) (12). For example, when CD8 − DCs take up antigen, they more efficiently form MHC II complexes (13) and elicit T cells producing IFN-γ and IL-4 (14,15).…”
mentioning
confidence: 99%